Melanins and melanogenesis: from pigment cells to human health and technological applications. (16th August 2015) - d'Ischia, Marco; Wakamatsu, Kazumasa; Cicoira, Fabio; Di Mauro, Eduardo; Garcia‐Borron, Josè Carlos; Commo, Stephane; Galván, Ismael; Ghanem, Ghanem; Kenzo, Koike; Meredith, Paul; Pezzella, Alessandro; Santato, Clara; et al.
Summary: During the past decade, melanins and melanogenesis have attracted growing interest for a broad range of biomedical and technological applications. The burst of polydopamine‐based multifunctional coatings in materials science is just one example, and the list may be expanded to include melanin thin films for organic electronics and bioelectronics, drug delivery systems, functional nanoparticles and biointerfaces, sunscreens, environmental remediation devices. Despite considerable advances, applied research on melanins and melanogenesis is still far from being mature. A closer intersectoral interaction between research centers is essential to raise the interests and increase the awareness of the biomedical, biomaterials science and hi‐tech sectors of the manifold opportunities offered by pigment cells and related metabolic pathways. Starting from a survey of biological roles and functions, the present review aims at providing an interdisciplinary perspective of melanin pigments and related pathway with a view to showing how it is possible to translate current knowledge about physical and chemical properties and control mechanisms into new bioinspired solutions for biomedical, dermocosmetic, and technological applications.